A review of the compulsory requirement for secondary level of education as under the Education Act 1996 [Act 550] / Adilita Alhawa Mohamed, Aida Anisa Md Salleh and Syazlin Mansor - Mohamed, Adilita Alhawa; Md Salleh, Aida Anisa; Mansor, Syazlin (2010)
This research concerns about the level of education in Malaysia which specifically deals with the primary compulsory education and non-secondary education. The compulsory education is a primary education is stated under Section 29A of the Education Act 1996 (Act 550). According to this section, parents may be punished if they failed to enroll their children to school, This however does not apply to the secondary level of education whereby under Section 30 of the same Act does not state the word "compulsory". The absence of a word "compulsory" in the provision regarding the secondary level of education in Malaysia has caused people to not take the matter of education after primary level seriously. Due to some factors and problems faced by the children, they decided to drop out of school. This might lead to heavier problems such as social illness, illiterate children, slowing down of economical growth and lower standard of living among members of society. Therefore, this research will focus on the need for an amendment of section 30 of Education Act 1996 (Act 550), which is to make the secondary level of education compulsory. This is to ensure that there will be no children dropping out off school, and preventing social illness, increase development of economic growth, thus creating a higher standard of society in Malaysia.